2017
DOI: 10.1371/journal.pone.0187913
|View full text |Cite
|
Sign up to set email alerts
|

Compatible bacterial mixture, tolerant to desiccation, improves maize plant growth

Abstract: Plant growth-promoting rhizobacteria (PGPR) increase plant growth and crop productivity. The inoculation of plants with a bacterial mixture (consortium) apparently provides greater benefits to plant growth than inoculation with a single bacterial strain. In the present work, a bacterial consortium was formulated containing four compatible and desiccation-tolerant strains with potential as PGPR. The formulation had one moderately (Pseudomonas putida KT2440) and three highly desiccation-tolerant (Sphingomonas sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(89 citation statements)
references
References 64 publications
5
73
0
1
Order By: Relevance
“…The inoculation of crop plants with beneficial microbes is a practice used in agriculture and provides advantages to crops by enhancing plant growth and triggering protection to diseases [55]. It was also reported that the inoculation with multiple beneficial bacteria have higher potential than inoculation with a single bacterial inoculant [12] [64]. Our study also showed the positive effects when the isolates were applied as a mixture from each location.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The inoculation of crop plants with beneficial microbes is a practice used in agriculture and provides advantages to crops by enhancing plant growth and triggering protection to diseases [55]. It was also reported that the inoculation with multiple beneficial bacteria have higher potential than inoculation with a single bacterial inoculant [12] [64]. Our study also showed the positive effects when the isolates were applied as a mixture from each location.…”
Section: Discussionsupporting
confidence: 61%
“…In this study, we aimed to examine bacterial community of sweet potato endophytes in Nepal in relation to the environmental parameters and characterize their plant growth promoting traits. As synergistic effect of mixed cultures of plant growth promoting bacteria was reported [11] [12], we also examined their potential by inoculating combined isolates from each location.…”
mentioning
confidence: 99%
“…In recent years, a large deal of literature has been produced on co-inoculation (consortium) of agriculturally beneficial microorganisms and in many cases benefits have been observed compared with the single inoculation (Akintokun and Taiwo, 2016;Sahu et al, 2016;Molina-Romero et al, 2017;Lally et al, 2017;Orozco-Mosqueda et al, 2018;Sahu et al, 2018). The present study shows that the beneficial endophytes E. cloacae RCA25 and H. huttiense RCA24 can be promising strains to improve, directly or indirectly, nitrogen fixation in rice plants under greenhouse conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, the outcome of the in vitro co-culture compatibility tests reflects the actual nature of the interaction to some extent (Prasad and Subramanian, 2017). For example, competitive colonization assays under controlled, greenhouse or fi eld conditions demonstrated that in vitro compatible bacterial and/or fungal stains are also compatible in the rhizosphere; root population levels reached by each strain in the mixture were not signifi cantly diff erent from those obtained when strains were applied individually (Agusti et al, 2011;Alizadeh et al, 2013;Stefanic et al, 2015;Castanheira et al, 2017;Molina-Romero et al, 2017;Santiago et al, 2017). The same goes with in vitro incompatible combinations.…”
Section: In Vitro Compatibility Of Pgpms In the Construction Of Multimentioning
confidence: 97%